Isolation and Purification of Fucoxanthin from Brown Seaweed Sargassum horneri Using Open ODS Column Chromatography and Ethanol Precipitation - Yuemei Ye; Jingwen Sun; Liting Wang; Junwang Zhu; Wei Cui; Hongyan Hou; Jinrong Zhang; Chengxu Zhou; Xiaojun Yan (Molecules, 2021)
As an abundant marine xanthophyll, fucoxanthin (FX) exhibits a broad range of biological activities. The preparation of high-purity FX is in great demand, however, most of the available methods require organic solvents which cannot meet the green chemistry standard. In the present study, a simple and efficient purification approach for the purification of FX from the brown seaweed Sargassum horneri was carried out. The FX-rich ethanol extract was isolated by octadecylsilyl (ODS) column chromatography using ethanol–water solvent as a gradient eluent. The overwhelming majority of FX was successfully eluted by the ethanol–water mixture (9:1, v/v), with a recovery rate of 95.36%. A parametric study was performed to optimize the aqueous ethanol precipitation process by investigating the effects on the purity and recovery of FX. Under the optimal conditions, the purity of FX was 91.07%, and the recovery rate was 74.98%. Collectively, the eco-friendly method was cost-efficient for the purification of FX. The developed method provides a potential approach for the large-scale production of fucoxanthin from the brown seaweed Sargassum horneri.